Austrian Students’ Perceptions of Social Distancing and Their Emotional Experiences During Distance Learning Due to the COVID-19 Pandemic - Heidrich, Franziska; Pozas, Marcela; Letzel, Verena; Lindner, Katharina-Theresa; Schneider, Christoph; Schwab, Susanne (Frontiers in Education, 2022)
The COVID-19 pandemic has led to far-reaching changes in various aspects of students’ lives. In the particular case of the educational field, classroom teaching was drastically shifted to a distance learning format. Consequently, students needed to deal with a completely different everyday school life. Learning was carried out online, which implied that students could not see some of their regular, important social contacts such as teachers, classmates or friends. It is already proven that such social distancing measures had impacts on students’ emotional experiences during the lockdown. Following a mixed-methods concurrent single-phase design, this study examined students’ perceptions of social distancing and their emotional experiences during the first school lockdown in Austria. Data from an online survey (n = 263 students) and from qualitative interviews (n = 56 students) were analyzed. The results show that distance learning drastically reduced interaction among students and between students and their teachers. Furthermore, the results indicate negative emotional experiences due to less social contact, increased learning pressures, and less structure. However, findings revealed that students also experience and perceived positive emotional experiences during distance learning because of more freedom, autonomy, and to some extent, less performance pressure. Based on the findings, the present study discusses possible perspectives on how to support students during and after distance learning, as well as further lines of research.